2015
DOI: 10.1002/ijc.29672
|View full text |Cite
|
Sign up to set email alerts
|

Fish, n − 3 polyunsaturated fatty acids and n − 6 polyunsaturated fatty acids intake and breast cancer risk: The Japan Public Health Center‐based prospective study

Abstract: Limited and inconsistent studies exist on the association between the intake of fish, n − 3 polyunsaturated fatty acids (PUFA) and n − 6 PUFA and breast cancer. Fish and n − 3 PUFA support various body functions and are thought to reduce the carcinogenesis risk while n − 6 PUFA may have a positive association with cancer risk. We examined the association between intake of fish, n − 3 PUFA [including eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), docosapentaenoic acid (DPA) and alpha‐linolenic acid (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 34 publications
5
42
3
Order By: Relevance
“…In total, forty-six [5,6,7,8,17,18,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60] independent prospective cohort studies were identified for meta-analysis. Among these articles, 15 were from the United States [7,8,18,21,24,26,31,34,37,39,40,49,52,55,60], 20 from Europe [5,6,22,23,25,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, forty-six [5,6,7,8,17,18,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60] independent prospective cohort studies were identified for meta-analysis. Among these articles, 15 were from the United States [7,8,18,21,24,26,31,34,37,39,40,49,52,55,60], 20 from Europe [5,6,22,23,25,…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen cohort studies [5,7,8,17,21,23,24,28,33,34,35,37,41,42,43,53,55,59] were included in the analysis, including 20,810 cases among 914,451 participants. The summary RR for highest versus lowest was 1.04 (95% CI 0.97–1.12) with moderate heterogeneity, I 2 = 47.9% (See Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis that included 11 prospective studies concluded that fish intake was not associated with BC risk [31]. Furthermore, a 2013 prospective study conducted among US black women also failed to find an association [32], as did a more recent prospective study conducted in Japan, where fish makes up a relatively higher proportion of daily dietary consumption [33]. In contrast, a prospective study from Denmark reported that overall intake of fish was associated with higher incidence rates of BC independently of fish fat content or preparation methods [34].…”
Section: Discussionmentioning
confidence: 99%
“…1). Finally, 24 independent studies from 23 articles 7,8,[10][11][12][13][14][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] (38,262 cases among 1,387,366 subjects) were included on dietary total fat and fatty acids intake, and seven articles [34][35][36][37][38][39][40] (1,334 cases among 3,511 subjects) were included on serum fatty acids.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%